Spontaneous Renal Artery Dissection in COVID-19 Pneumonia: Potential Danger of Cytokine Storm - Jitendra Parmar; Tapan Patel; Sandip Shah; Jay Kothari; Sameer Dani; Sagar Vyas (Case Reports in Critical Care)
The coronavirus disease (COVID-19) pandemic has rapidly spread across the globe since its first detection in March 2020. Its widespread manifestations and vascular complications are increasingly being reported even in young and middle-aged patients. Hyperinflammation is a continuum of host’s exaggerated inflammatory response representing cytokine dysregulation/storm which produces coagulopathy and vascular endothelial dysfunction, apart from a prothrombotic state. Cytokine storm or direct viral invasion of the vascular endothelial cells through surface angiotensin-converting enzyme 2 receptors may result in endothelial dysfunction which can potentially result in dissection. Only a few case reports have been published in the literature describing vascular dissection without any inciting factors in COVID-19 patients. Herein, we present the first case report of bilateral renal artery dissection in a 41-year-old male patient who recently recovered from COVID-19 and was managed successfully in stages after many medical hurdles.